2017
DOI: 10.1111/ajps.12297
|View full text |Cite
|
Sign up to set email alerts
|

The Vicarious Bases of Perceived Injustice

Abstract: Profound differences exist in how Americans from various racial and ethnic groups view police and court officials. We argue that vicarious experiences contribute to this racial and ethnic divide. Drawing on research on social communication, social network composition, and negativity biases in perception and judgment, we devise a theoretical framework to articulate why vicarious experiences magnify racial and ethnic disparities in evaluations of judicial actors. Four hypotheses are tested using original survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
(36 reference statements)
2
22
0
Order By: Relevance
“…Duch and Stevenson, 2011). Outside of the realm of economic voting, scholars have demonstrated that personal (Tyler, 1990) and vicarious (Mondak et al 2017b;Peffley and Hurwitz, 2010) experiences affect people's perceptions of the justice system. 14 We see a subnational focus as valuable, but why at the regional level?…”
Section: Connecting Bribery Experiences and Corruption Perceptionmentioning
confidence: 99%
“…Duch and Stevenson, 2011). Outside of the realm of economic voting, scholars have demonstrated that personal (Tyler, 1990) and vicarious (Mondak et al 2017b;Peffley and Hurwitz, 2010) experiences affect people's perceptions of the justice system. 14 We see a subnational focus as valuable, but why at the regional level?…”
Section: Connecting Bribery Experiences and Corruption Perceptionmentioning
confidence: 99%
“…White Americans are least likely to experience immigration enforcement, most likely to view unfair treatment by law enforcement as exceptional (Peffley and Hurwitz 2010), and are less likely to have antagonistic criminal legal experiences than are Blacks and Latinos (Mondak et al 2017). Nevertheless, although researchers find that whites have a lower baseline level of racial empathy than do Black Americans (Sirin, Valentino, and Villalobos 2017), it may be the case that proximal experiences with immigration educate white Americans and tap a sense of empathy like their Black counterparts.…”
Section: The Nature Of Race and Injusticementioning
confidence: 99%
“…The group consciousness literature nevertheless offers insight into how we might expect racial subgroups to respond to proximal contact with immigration enforcement. Race structures interactions with law enforcement of all types (Maltby 2017), where whites are much less likely to have any type of contact and more likely to know people who have had positive interactions with the system than are Blacks and Latinos, whose personal and proximal experiences are more likely to be antagonistic (Mondak et al 2017). Moreover, each racial subgroup has very different histories with institutional and social exclusion more generally, and the extent to which individuals view experiences with immigration as systemically unfair should likewise vary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have likewise tried to understand the civic consequences of officer-involved shootings, where responses to such incidents appear most vividly via protest, marked especially by the rise of the movement for Black lives (Cohen et al 2019; Williamson et al 2018). Research examining the civic consequences of having a relational connection to a custodial citizen finds that the policy feedback effects of contact identified by Lerman and Weaver (2014a) spill over to those who experience the system vicariously, albeit in sometimes unexpected ways (Anoll and Israel-Trummel 2019; Mondak et al 2017; Lee, Porter, and Comfort 2014; Walker 2014; 2020). While scholars largely draw on survey data to identify people with proximal criminal legal connections, the use of administrative records to identify these same people is one of the most exciting developments in this line of inquiry (White 2018).…”
Section: How Marginalized People View the Criminal Legal Systemmentioning
confidence: 99%